Pengaruh Self-Attribution Bias terhadap Perilaku Investor dengan Overconfidence Bias sebagai Variabel Intervening - Anisa Kusumawardani; Eka Yuliyanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
"This research aims to reveal the influence of Self-Attribution Bias on in decision-making mediated by Overconfidence Bias. This type of research is causal associative. The study population includes various stock communities in Indonesia. The sampling technique used is purposive sampling. The obtained sample consists of 103 participants, and the questionnaire distribution process took place from November to December 2023. The data analysis method used is Partial Least Squares. Based on the research findings, it is indicated that: (1) Self-Attribution Bias influences Investor Behavior in Decision-Making, (2) Self-Attribution Bias does not influence Overconfidence Bias, (3) Overconfidence Bias influences Investor Behavior, (4) Self-Attribution Bias influences Investor Behavior with Overconfidence Bias as an intervening variable."